Isolation and purification of pinellic acid from Pinellia Ternata - Cornelia, Chin Siew Ling (2012)
Pinellia ternata is a perennial herb belonging to the Araceae family. Pinellia ternata is a plant native to Japan, but also grows as a weed in certain areas of North America. It is commonly used as one of the main components in many decoctions in traditional Chinese medicine that has been used widely for thousands of years in China to prevent vomiting and for analgesic and sedative effects. Pinellia ternata is an active herbal component of the traditional Japanese herbal (Kampo) medicine, Sho-seiryu-to (SST) (Chinese name: Xiao-Qing-Long-Tang), and it has been reported to show oral adjuvant activity for nasally administered influenza hemagglutinin (HA) vaccine. The active compound that displayed adjuvant properties was identified as 9S, 12S, 13S-trihydroxy-1OEoctadecenoic acid commonly known as Pinellic acid. This research was conducted with a goal to isolate and purify Pinellic Acid (9S, 12S, 13S-trihydroxy-1OEoctadecenoic acid) from Pinellia ternata plant. Pinellia ternata was extracted with two types of solvent; water and methanol. The extracts were purified with Hydrophobic Interaction Chromatography with methanol as the polar eluent and Column Chromatography with the solvent system hexane-ethyl acetate. The pure Pinellic acid obtained was determined by Reversed phase High Performance Liquid Chromatography (RP-HPLC) using 70% methanol containing 0.01% acetic acid as the solvent system; and Infrared Spectroscopy. Highest % yield of Pinellic acid calculated was obtained from the sample extracted with methanol. High Performance Liquid Chromatography analysis for methanol-extract gave a clear single peak at 4.11 minutes at a flow rate of 1 ml/min. The compound obtained has displayed solvent selectivity towards methanol as opposed to water.